Method for preparing refractory high-entropy alloy coating through pulse laser-assisted laser-induction composite cladding

By introducing pulsed laser and induction heat sources into laser cladding technology, the cracks and pore problems of laser cladding technology when processing refractory high-entropy alloys are solved, and the grain refinement and processing efficiency are significantly improved.

CN119615145AInactive Publication Date: 2025-03-14JINAN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411399137.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-03-14
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

When processing refractory high-entropy alloys, laser cladding technology leads to the formation of cracks and pores due to the stress problems caused by large temperature gradients and different thermal expansion coefficients, which limits its application in the industrial field.

Method used

Pulse laser-assisted laser-induction composite cladding technology is used to reduce the temperature gradient through induction heat source, and use the shock wave generated by high-frequency pulsed laser to stir the melt pool to accelerate convection and heat transmission, break down dendrites, refine grains, and reduce the formation of cracks and holes.

Benefits of technology

It effectively inhibits the formation of cracks and holes, significantly refines the grains, improves the quality and processing efficiency of the coating, improves the processing efficiency by more than 8 times, and refines the grain size by more than 73%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615145A_ABST
    Figure CN119615145A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of refractory high-entropy alloys, and particularly relates to a method for preparing a refractory high-entropy alloy coating through pulse laser-assisted laser-induction composite cladding. According to the method, a continuous laser heat source is mainly used, an induction heat source and a high-frequency pulse laser heat source are introduced in the cladding process, and the high-quality refractory high-entropy alloy coating is prepared. According to the method, the temperature gradient is reduced through induction heating, thermally induced stress is restrained, shock waves generated by high-frequency pulse laser are used for conducting high-frequency stirring on a molten pool, molten pool convection and heat transmission are accelerated, heat distribution homogenization in the molten pool is promoted, the temperature gradient is reduced, and formation of cracks, holes and other defects is effectively restrained; the grain size of a cladding layer is refined by 73% or above, and the machining efficiency is improved by 8 times or above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of refractory high entropy alloys, and in particular relates to a method for preparing a refractory high entropy alloy coating by pulse laser assisted laser-induction composite cladding. Background Art

[0002] Refractory high entropy alloys are new high entropy alloys with refractory metal elements such as Ti, Zr, Nb, Ta, Mo, and W as the main elements. With excellent high-temperature mechanical properties, refractory high entropy alloys have broad application prospects in high-temperature fields such as aerospace, petrochemicals, and nuclear reactors. However, the high melting point of refractory elements and the large difference in melting points between elements have great limitations in processing and preparation. Compared with traditional preparation methods such as arc melting and powder metallurgy, laser cladding technology has the advantages of rapid heating and cooling, high energy density, and small heat-affected zone. It can quickly melt the substrate surface and powder through a high-energy laser beam to form a cladding layer. However, the temperature gradient of the laser cladding process is large and the thermal expansion coefficients between the substrate and the cladding powder are different, which leads to large stresses during the forming process and then cracks, which seriously limits the application and development of laser cladding technology in the industrial field.

[0003] Laser-induction composite cladding technology combines laser heat source with high-frequency induction heat source. While maintaining the high energy density of laser cladding, it introduces induction heat source to deliver part of the energy to the substrate, effectively reducing the temperature gradient of the cladding process, residual stress, and crack sensitivity while improving the processing efficiency by 1 to 5 times. However, laser-induction composite cladding cannot control the convection and heat and mass transfer behavior inside the molten pool, which has certain limitations on improving the coating quality. In addition, its processing efficiency is still low, and it is impossible to further refine the grains.

[0004] High-frequency pulsed laser can cause the top of the molten pool to evaporate and ionize to form plasma. As the plasma rapidly heats and expands, shock waves are generated on the surface of the molten pool and propagate into the inside of the molten pool, subjecting the molten pool to high-frequency shock vibration, stirring the molten pool and accelerating convection in the molten pool, effectively inhibiting the formation of defects such as cracks and pores. In addition, dendrites are broken and dispersed under the action of high-frequency vibration, acting as heterogeneous nucleation cores and refining grains. At the same time, pulsed lasers can output higher energy in a short time. This energy is superimposed with the energy output by continuous laser heat sources and induction heat sources, which can greatly improve processing efficiency. However, there are currently no literature reports on pulsed laser-assisted laser-induction composite cladding of refractory high-entropy alloy coatings. Summary of the invention

[0005] In order to solve the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a method for preparing a refractory high entropy alloy coating by pulsed laser-assisted laser-induction composite cladding. The method introduces an induction heat source and a pulsed laser heat source during the laser cladding process, and uses the induction heat source to reduce the temperature gradient and eliminate cracks in the cladding layer. At the same time, the shock wave generated by the high-frequency pulsed laser stirs the molten pool and accelerates the convection and heat transfer of the molten pool, promotes the uniformity of heat distribution in the molten pool, and breaks up dendrites, thereby achieving the purpose of eliminating pores and cracks, refining grains, and improving processing efficiency.

[0006] The purpose of the present invention is achieved through the following technical solutions: A method for preparing a refractory high entropy alloy coating by pulse laser assisted laser-induction composite cladding, comprising the following steps: Step 1: Pre-treat the surface of the substrate; Step 2: placing the refractory high entropy alloy powder in a loading hopper of an automatic powder feeder; Step 3: Adjust the distance between the center of the induction heating coil and the surface of the substrate so that the substrate can be effectively heated by the surface skin effect; Step 4: Adjust the position of the induction coil so that the continuous laser beam spot and the powder nozzle are located within the induction heating area; Step 5: Introduce pulsed laser to regulate the molten pool morphology and molten pool convection, adjust the pulsed laser beam position, make the pulsed laser beam spot coincide with the center of the continuous laser beam spot, at this time the pulsed laser beam spot is completely inside the continuous laser beam spot and directly acts on the molten pool, realizing the coupling of pulsed laser heat source, continuous laser heat source and induction heat source; the pulsed laser head and the continuous laser head are installed on the robot arm and move synchronously to realize dual-beam coupling; Step 6: After each cladding layer, adjust the position of the continuous laser heat source, induction heat source and pulsed laser heat source to return to the processing starting position of the current layer, and rise one cladding layer height along the Z axis, and then repeat steps 3 to 5 until the desired thickness of the coating is obtained.

[0007] Preferably, the pretreatment in step 1 includes: polishing the surface of the substrate to remove surface rust and oxide film, then ultrasonically cleaning with ethanol to remove surface oil, and drying after cleaning for later use.

[0008] Preferably, the substrate in step 1 is a titanium alloy.

[0009] Preferably, the chemical composition of the refractory high entropy alloy powder in step 2 is: Nb 16.83~24.83 at%, Mo 16.83~24.83 at%, Ti 16.83~24.83 at%, V 16.83~24.83 at%, Al 8.42~12.42 at%, Si 5.25~7.25 at%.

[0010] Preferably, in step 3, the distance between the induction heating coil and the surface of the substrate is 3-12 mm, and the surface of the substrate is heated to 300-1200°C.

[0011] Preferably, the continuous laser beam described in step 4 has a laser power of 2-20 kW, a laser scanning speed of 3-15 m / min, a spot diameter of 2-6 mm, a powder feeding amount of 150-300 g / min, an overlap rate of 40-60%, and a single layer thickness of 0.1-2 mm.

[0012] Preferably, in step 5, high-purity argon gas is introduced as a protective gas and a powder carrier to prevent oxidation of the powder during the cladding process, and the flow rate of the high-purity argon gas is 15-20 L / min.

[0013] More preferably, in step 5, an oxygen content detector is used to detect the oxygen content in real time to ensure that the oxygen content is less than 5 ppm during the cladding process.

[0014] More preferably, the high-purity argon gas refers to argon gas with a purity higher than 99.999%.

[0015] Preferably, the pulse laser in step 5 has an average pulse laser power of 200-1000 W, a pulse width of 50-200 ns, a pulse frequency of 15-100 kHz, and a pulse laser beam spot diameter of 0.5-3 mm. In this step, the temperature gradient is reduced by induction heating to suppress thermal stress, and the shock wave generated by the high-frequency pulse laser is used to stir the molten pool at high frequency, accelerate the convection and heat transfer of the molten pool, promote the uniformity of heat distribution in the molten pool, reduce the temperature gradient, and effectively suppress the formation of defects such as cracks and holes, so as to achieve a grain size refinement of more than 73% in the cladding layer and improve the processing efficiency by more than 8 times. Within the above parameter range, the prepared coating has the best performance.

[0016] Preferably, the thickness of the coating in step 6 is 2 to 10 mm.

[0017] Compared with the prior art, the present invention has the following advantages and beneficial effects: 1. The present invention adopts a combination of three heat sources: continuous laser heat source, induction heat source and pulse laser heat source. The processing efficiency is increased by more than 8 times compared with traditional laser cladding.

[0018] 2. The present invention mainly uses a continuous laser heat source, supplemented by an induction heat source and a pulsed laser heat source. The introduction of the induction heat source effectively reduces the large temperature gradient under the high-energy laser beam, inhibits the generation of thermally induced stress and thus reduces crack sensitivity. At the same time, the shock wave generated by the high-frequency pulsed laser stirs the molten pool at high frequency, accelerates the convection and heat transfer of the molten pool, promotes the uniformity of heat distribution in the molten pool, reduces the temperature gradient, and effectively inhibits the formation of defects such as cracks and holes.

[0019] 3. The present invention uses shock waves generated by high-frequency pulsed lasers to stir the molten pool at high frequency, thereby breaking and dispersing the dendrites, thereby increasing heterogeneous nucleation sites and promoting grain refinement. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 Refractory high entropy alloy coating cross-sectional morphologies, wherein (a) to (c) are cross-sectional morphologies of refractory high entropy alloy coatings prepared in Example 1, Example 2, and Example 3, respectively, and (d) is a cross-sectional morphology of a refractory high entropy alloy coating prepared in Comparative Example 1.

[0021] Figure 2 Refractory high entropy alloy coating grain map, wherein (a) is the refractory high entropy alloy coating grain map prepared in comparative example 1, and (b) is the refractory high entropy alloy coating grain map prepared in example 2. DETAILED DESCRIPTION

[0022] The present invention is further described in detail below in conjunction with the examples and drawings, but the embodiments of the present invention are not limited thereto. The raw materials involved in the present invention can be purchased directly from the market. For process parameters not particularly noted, conventional techniques can be used.

[0023] Example 1 Step 1: Before processing, the substrate surface is polished to remove surface rust and oxide film, and then ultrasonically cleaned with ethanol to remove surface oil stains. After cleaning, it is dried in a vacuum drying oven for later use; Step 2: placing refractory high entropy alloy powder in a loading hopper of an automatic powder feeder; wherein the chemical composition of the refractory high entropy alloy powder is: Nb 21.05 at%, Mo 21.05 at%, Ti 21.05 at%, V21.05 at%, Al 10.54 at%, Si 5.26 at%; Step 3: Adjust the distance between the center of the induction heating coil and the surface of the substrate so that the substrate can be effectively heated by the surface skin effect; wherein the distance between the induction heating coil and the surface of the substrate is 5 mm, and the surface of the substrate is heated to 900 °C; Step 4: Adjust the position of the induction coil so that the continuous laser beam spot and the powder nozzle are located in the induction heating area, the laser power is 3 kW, the laser scanning speed is 4 m / min, the spot diameter is 3 mm, the powder feeding amount is 180 g / min, the overlap rate is 40%, and the single layer thickness is 0.8 mm; Step 5: Introduce pulsed laser to regulate the molten pool morphology and molten pool convection, adjust the pulsed laser beam position, make the pulsed laser beam spot coincide with the center of the continuous laser beam spot, at this time the pulsed laser beam spot is completely inside the continuous laser beam spot and directly acts on the molten pool, realizing the coupling of pulsed laser heat source, continuous laser heat source and induction heat source. The pulsed laser head and the continuous laser head are installed on the robot arm and move synchronously. High-purity argon is used as the protective gas and powder carrier, and the oxygen content detector is used to detect the oxygen content in real time to ensure that the oxygen content is less than 5 ppm during the cladding process to prevent powder oxidation during the cladding process. The high-purity argon flow rate is 15 L / min. By adjusting the parameters such as the pulsed laser beam power, width and frequency, the stirring and convection of the molten pool are regulated to improve the fluidity of the molten pool, reduce the temperature gradient in the molten pool, reduce the residual stress, and achieve the purpose of eliminating cracks and pores and refining the grains. Among them, the average laser power is 500 W, the pulse width is 120 ns, the pulse frequency is 50 kHz, and the spot diameter is 0.5 mm; Step 6: After each cladding layer, adjust the position of the continuous laser heat source, induction heat source and pulsed laser heat source to return to the processing starting position of the current layer, and rise one cladding layer height along the Z axis, and then repeat steps 3 to 5 until a coating with a thickness of 8 mm is obtained.

[0024] The cross-sectional morphology of the refractory high entropy alloy coating prepared by pulsed laser assisted laser-induction composite cladding in this example is as follows: Figure 1 As shown in (a), Figure 1 (d) is the refractory high entropy alloy coating prepared by conventional laser cladding in Comparative Example 1. By comparison, it is found that Figure 1 In (d), large-sized cracks and pores can be observed, while the refractory high-entropy alloy coating prepared in this embodiment has no obvious defects such as cracks and pores, indicating that the introduction of induction heat source and pulsed laser heat source can effectively inhibit the formation of defects such as cracks and holes. From the EBSD test, it can be seen that the average grain size of the cladding layer of the refractory high-entropy alloy coating prepared in this embodiment is 18.52 μm, while the average grain size of the cladding layer of the refractory high-entropy alloy coating prepared in Comparative Example 1 is 70.94 μm. Compared with Comparative Example 1, the average grain size of the refractory high-entropy alloy coating prepared in this embodiment is reduced by 73.89%. Nanoindentation test was performed along the depth direction of the cladding layer. The results are shown in Table 1. The average nanohardness and Young's modulus of the refractory high entropy alloy coating sample prepared by the pulsed laser and induction heat source in this embodiment are 8.75 GPa and 195.11 GPa, respectively, which are 8.97% and 11.57% higher than the average nanohardness (8.03 GPa) and Young's modulus (174.88 GPa) of the refractory high entropy alloy coating sample prepared by traditional laser cladding. At the same time, the processing efficiency is 8.5 times higher than that of traditional laser cladding.

[0025] Example 2 Step 1: Before processing, the substrate surface is polished to remove surface rust and oxide film, and then ultrasonically cleaned with ethanol to remove surface oil stains. After cleaning, it is dried in a vacuum drying oven for later use; Step 2: placing refractory high entropy alloy powder in a loading hopper of an automatic powder feeder; wherein the chemical composition of the refractory high entropy alloy powder is: Nb 21.05 at%, Mo 21.05 at%, Ti 21.05 at%, V21.05 at%, Al 10.54 at%, Si 5.26 at%; Step 3: Adjust the distance between the center of the induction heating coil and the surface of the substrate so that the substrate can be effectively heated by the surface skin effect; wherein the distance between the induction heating coil and the surface of the substrate is 6 mm, and the surface of the substrate is heated to 800 °C; Step 4: Adjust the position of the induction coil so that the continuous laser beam spot and the powder nozzle are located in the induction heating area, the laser power is 6 kW, the laser scanning speed is 12 m / min, the spot diameter is 5 mm, the powder feeding amount is 300 g / min, the overlap rate is 50%, and the single layer thickness is 0.2 mm; Step 5: Introduce pulsed laser to regulate the molten pool morphology and molten pool convection, adjust the pulsed laser beam position, make the pulsed laser beam spot coincide with the center of the continuous laser beam spot, at this time the pulsed laser beam spot is completely inside the continuous laser beam spot and directly acts on the molten pool, realizing the coupling of pulsed laser heat source, continuous laser heat source and induction heat source. The pulsed laser head and the continuous laser head are installed on the robot arm and move synchronously. High-purity argon is used as the protective gas and powder carrier, and the oxygen content detector is used to detect the oxygen content in real time to ensure that the oxygen content is less than 5 ppm during the cladding process to prevent powder oxidation during the cladding process. The high-purity argon flow rate is 15 L / min. By adjusting the parameters such as the pulsed laser beam power, width and frequency, the stirring and convection of the molten pool are regulated to improve the fluidity of the molten pool, reduce the temperature gradient in the molten pool, reduce the residual stress, and achieve the purpose of eliminating cracks and pores and refining the grains. Among them, the average laser power is 500 W, the pulse width is 150 ns, the pulse frequency is 25 kHz, and the spot diameter is 1.5 mm; Step 6: After each cladding layer, adjust the position of the continuous laser heat source, induction heat source and pulsed laser heat source to return to the processing starting position of the current layer and rise one cladding layer height along the Z axis, and then repeat steps 3 to 5 until a coating with a thickness of 5 mm is obtained.

[0026] The cross-sectional morphology of the refractory high entropy alloy coating prepared by pulsed laser assisted laser-induction composite cladding in this example is as follows: Figure 1 As shown in (b), Figure 1(d) is the refractory high entropy alloy coating prepared by conventional laser cladding in Comparative Example 1. By comparison, it is found that Figure 1 In (d), large-sized cracks and pores can be observed, while the refractory high-entropy alloy coating prepared in this embodiment has no obvious defects such as cracks and pores, indicating that the introduction of induction heat source and pulsed laser heat source can effectively inhibit the formation of defects such as cracks and holes. From the EBSD test, it can be seen that the average grain size of the cladding layer of the refractory high-entropy alloy coating prepared in this embodiment is 8.97 μm, while the average grain size of the cladding layer of the refractory high-entropy alloy coating prepared in Comparative Example 1 is 70.94 μm. Compared with Comparative Example 1, the average grain size of the refractory high-entropy alloy coating prepared in this embodiment is reduced by 87.36%. Nanoindentation test was performed along the depth direction of the cladding layer. The results are shown in Table 1. The average nanohardness and Young's modulus of the refractory high entropy alloy coating sample prepared by the pulsed laser and induction heat source in this embodiment are 8.98 GPa and 196.27 GPa, respectively, which are 11.83% and 12.09% higher than the average nanohardness (8.03 GPa) and Young's modulus (174.88 GPa) of the refractory high entropy alloy coating sample prepared by traditional laser cladding. At the same time, the processing efficiency is 11.3 times higher than that of traditional laser cladding.

[0027] Example 3 Step 1: Before processing, the substrate surface is polished to remove surface rust and oxide film, and then ultrasonically cleaned with ethanol to remove surface oil stains. After cleaning, it is dried in a vacuum drying oven for later use; Step 2: placing refractory high entropy alloy powder in a loading hopper of an automatic powder feeder; wherein the chemical composition of the refractory high entropy alloy powder is: Nb 21.05 at%, Mo 21.05 at%, Ti 21.05 at%, V 21.05 at%, Al10.54 at%, Si5.26 at%; Step 3: Adjust the distance between the center of the induction heating coil and the surface of the substrate so that the substrate can be effectively heated by the surface skin effect; wherein the distance between the induction heating coil and the surface of the substrate is 7 mm, and the surface of the substrate is heated to 700 °C; Step 4: Adjust the position of the induction coil so that the continuous laser beam spot and the powder nozzle are located in the induction heating area, the laser power is 9 kW, the laser scanning speed is 8 m / min, the spot diameter is 2.5 mm, the powder feeding amount is 240 g / min, the overlap rate is 45%, and the single layer thickness is 0.6 mm; Step 5: Introduce pulsed laser to regulate the molten pool morphology and molten pool convection, adjust the pulsed laser beam position, make the pulsed laser beam spot coincide with the center of the continuous laser beam spot, at this time the pulsed laser beam spot is completely inside the continuous laser beam spot and directly acts on the molten pool, realizing the coupling of pulsed laser heat source, continuous laser heat source and induction heat source. The pulsed laser head and the continuous laser head are installed on the robot arm and move synchronously. High-purity argon gas is used as the protective gas and powder carrier, and the oxygen content detector is used to detect the oxygen content in real time to ensure that the oxygen content is less than 5 ppm during the cladding process to prevent powder oxidation during the cladding process. The high-purity argon gas flow rate is 15 L / min. By adjusting the parameters such as the pulsed laser beam power, width and frequency, the stirring and convection of the molten pool are regulated to improve the fluidity of the molten pool, reduce the temperature gradient in the molten pool, reduce the residual stress, and achieve the purpose of eliminating cracks and pores and refining the grains. Among them, the average laser power is 600 W, the pulse width is 120 ns, the pulse frequency is 40 kHz, and the spot diameter is 1 mm; Step 6: After each cladding layer, adjust the position of the continuous laser heat source, induction heat source and pulsed laser heat source to return to the processing starting position of the current layer and rise one cladding layer height along the Z axis, and then repeat steps 3 to 5 until a coating with a thickness of 6 mm is obtained.

[0028] The cross-sectional morphology of the refractory high entropy alloy coating prepared by pulsed laser assisted laser-induction composite cladding in this example is as follows: Figure 1 As shown in (c), Figure 1 (d) is the refractory high entropy alloy coating prepared by conventional laser cladding in Comparative Example 1. By comparison, it is found that Figure 1 In (d), large-sized cracks and pores can be observed, while the refractory high-entropy alloy coating prepared in this embodiment has no obvious defects such as cracks and pores, indicating that the introduction of induction heat source and pulsed laser heat source can effectively inhibit the formation of defects such as cracks and holes. From the EBSD test, it can be seen that the average grain size of the cladding layer of the refractory high-entropy alloy coating prepared in this embodiment is 10.16 μm, while the average grain size of the cladding layer of the refractory high-entropy alloy coating prepared in Comparative Example 1 is 70.94 μm. Compared with Comparative Example 1, the average grain size of the refractory high-entropy alloy coating prepared in this embodiment is reduced by 85.68%. Nanoindentation test was performed along the depth direction of the cladding layer. The results are shown in Table 1. The average nanohardness and Young's modulus of the refractory high entropy alloy coating sample prepared by the pulsed laser and induction heat source in this embodiment are 9.13 GPa and 197.21 GPa, respectively, which are 13.70% and 12.77% higher than the average nanohardness (8.03 GPa) and Young's modulus (174.88 GPa) of the refractory high entropy alloy coating sample prepared by traditional laser cladding. At the same time, the processing efficiency is 9.8 times higher than that of traditional laser cladding.

[0029] Comparative Example 1: Preparation of coating by conventional laser cladding method Step 1: Before processing, the substrate surface is polished to remove surface rust and oxide film, and then ultrasonically cleaned with ethanol to remove surface oil stains. After cleaning, it is dried in a vacuum drying oven for later use; Step 2: placing refractory high entropy alloy powder in a loading hopper of an automatic powder feeder; wherein the chemical composition of the refractory high entropy alloy powder is: Nb 21.05 at%, Mo 21.05 at%, Ti 21.05 at%, V21.05 at%, Al 10.54 at%, Si 5.26 at%; Step 3: Use high-purity argon as the protective gas and powder carrier, the high-purity argon flow rate is 15 L / min, the laser power is 2 kW, the laser scanning speed is 3 m / min, the spot diameter is 3 mm, the powder feeding amount is 15 g / min, the overlap rate is 45%, and the single layer thickness is 0.8 mm; Step 4: After each cladding layer, adjust the position of the continuous laser heat source to increase the height of one cladding layer, and then repeat step 3 until a coating with a thickness of 6 mm is obtained.

[0030] Table 1 shows the hardness H, elastic modulus E, elastic strain failure H / E and yield pressure H3 / E2 values ​​of the refractory high entropy alloy coatings prepared in the embodiments of the present invention and the comparative examples. By comparison, it is found that the introduction of the induction heat source and the pulsed laser heat source significantly improves the H, E, H / E and H3 / E2 of the coating. Generally, high hardness and high Young's modulus represent better wear resistance. In addition, elastic strain failure H / E and yield pressure H3 / E2 are also related to wear characteristics. High elasticity and high yield pressure indicate that the material has a stronger ability to resist plastic deformation, that is, the better the wear resistance.

[0031] Table 1 Hardness of coating H , elastic modulus E , elastic strain failure H / E Yield Pressure H 3 / E 2 and the average grain size The hardness and elastic modulus of the coatings were measured using a nanoindenter as shown in Table 1, where the maximum load was set to 50 mN and ten points were measured for each sample to ensure data reliability.

[0032] Figure 1The cross-sectional morphology of the refractory high entropy alloy coating, wherein (a) to (c) are the cross-sectional morphology of the refractory high entropy alloy coating prepared in Example 1, Example 2 and Example 3, respectively, and (d) is the cross-sectional morphology of the refractory high entropy alloy coating prepared in Comparative Example 1. It can be seen that the coating prepared by traditional laser cladding has large-sized cracks and holes, and after the introduction of induction heat source and pulsed laser, the quality of the cladding layer is significantly improved, and no obvious defects such as cracks and holes are found in the cross section.

[0033] Figure 2 refractory high entropy alloy coating grain map, wherein (a) is the refractory high entropy alloy coating grain map prepared in comparative example 1, it can be seen that the cladding layer has coarse grains, and the average grain size is 70.94 μm; (b) is the refractory high entropy alloy coating grain map prepared in example 2, it can be seen that the introduction of the induction heat source and the pulsed laser effectively promotes the grain refinement, and the average grain size is reduced to 8.97 μm.

[0034] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principles of the present invention shall be equivalent replacement methods and shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a refractory high entropy alloy coating by pulsed laser-assisted laser-induction composite cladding, characterized in that: The following steps are involved: Step 1: Pre-treat the surface of the substrate; Step 2: placing the refractory high entropy alloy powder in a loading hopper of an automatic powder feeder; Step 3: Adjust the distance between the center of the induction heating coil and the surface of the substrate so that the substrate can be effectively heated by the surface skin effect; Step 4: Adjust the position of the induction coil so that the continuous laser beam spot and the powder nozzle are located within the induction heating area; Step 5: Introduce pulsed laser, adjust the position of pulsed laser beam, make the center of pulsed laser beam spot coincide with the center of continuous laser beam spot, realize the coupling of pulsed laser heat source, continuous laser heat source and induction heat source; the pulsed laser head and continuous laser head are installed on the robot arm and move synchronously; Step 6: After each cladding layer, adjust the position of the continuous laser heat source, induction heat source and pulsed laser heat source to return to the processing starting position of the current layer, and rise one cladding layer height along the Z axis, and then repeat steps 3 to 5 until the desired thickness of the coating is obtained.

2. The method according to claim 1, characterized in that: The pretreatment in step 1 includes: polishing the surface of the substrate to remove surface rust and oxide film, then ultrasonically cleaning with ethanol to remove surface oil, and drying after cleaning for later use; the substrate is a titanium alloy.

3. The method according to claim 1, characterized in that The chemical composition of the refractory high entropy alloy powder in step 2 is: Nb 16.83~24.83 at%, Mo 16.83~24.83 at%, Ti 16.83~24.83 at%, V 16.83~24.83 at%, Al 8.42~12.42 at%, Si 5.25~7.25 at%.

4. The method according to claim 1, characterized in that In step 3, the distance between the induction heating coil and the substrate surface is 3-12 mm, and the substrate surface is heated to 300-1200°C.

5. The method according to claim 1, characterized in that The continuous laser beam described in step 4 has a laser power of 2~20kW, a laser scanning speed of 3~15 m / min, a spot diameter of 2~6 mm, a powder feeding amount of 150~300 g / min, an overlap rate of 40~60%, and a single layer thickness of 0.1~2 mm.

6. The method according to claim 1, characterized in that In step 5, high-purity argon gas is introduced as a protective gas and a powder carrier, and the flow rate of the high-purity argon gas is 15-20 L / min.

7. The method according to claim 6, characterized in that In step 5, an oxygen content detector is used to detect the oxygen content in real time to ensure that the oxygen content is less than 5 ppm during the cladding process.

8. The method according to claim 6, characterized in that The high-purity argon gas refers to argon gas with a purity higher than 99.999%.

9. The method according to claim 1, characterized in that: The pulse laser described in step 5 has an average pulse laser power of 200-1000 W, a pulse width of 50-200 ns, a pulse frequency of 15-100 kHz, and a pulse laser beam spot diameter of 0.5-3 mm.

10. The method according to claim 1, characterized in that The thickness of the coating in step 6 is 2 to 10 mm.